Decomposition model of representation of semantic constants and variables for implementation of examinations in the TPI sphere - Корченко, Олександр Григорович; Давиденко, Анатолій Миколайович; Шабан, Максим Радуйович (Ukrainian Information Security Research Journal, 2019)
State expertise is a lengthy process and is associated with possible errors both at the stage of the design work and during the examination itself. Therefore, the actual scientific task is to create an information system that would help the expert in building output documents, and also allow the expert to check the functional protection profile (FPP). The paper proposes a decomposition model, which, due to the formed sets of input and output documents of the p-th project, as well as plural semantic blocks, semantic constants and variables of the p-th project, allows automating the process of identifying the FPP. To do this, we decomposed the output documents, taking into account the stages of the formation of sets of examination documents, the structure of semantic blocks, the semantic variables of output documents. Analyze the principles of the organization of the structure of documents that are created at the stage of state examination of integrated information protection systems (IIPS). Introduce the concept of semantic blocks, semantic constants, semantic variables. The semantic block is a permanent semantic construction that has a complete semantic meaning. The semantic constant is a stable semantic construction, the existence of which goes beyond the framework of the state expert review of the IIPS. In turn, the semantic variable is a semantic construction, the time of its existence is equal to the time of the state examination of the IIPS. All this has allowed to speed up the process of creating output documents of state expert reviews of the IIPS. The development of these works is the development of the method of identification of the FPP. This will allow to formalize the requirements of the regulatory document in relation to its properties, which will be done in future articles